Performance Management in Light Industrial Companies in Shanghai - Ying, Haoyuan (2006)
With the development of global economy, the competition becomes more and more intense. The core turns to the human resources (i.e. employees), while performance management is the tool introduced to manage the employees' performance so as to realize the objectives of organizations. Through the review of literature on this field, the effectiveness of performance management remains arguable. Thus the research is to examine whether the performance management implemented in real world is effective. The targets are three light industrial companies in Shanghai: Alcoa Shanghai Aluminum Products Co., Ltd., Shanghai Gillette Co., Ltd. and Zwilling J.A. Henckels Shanghai Ltd. Through analyzing the results of interview, case study and documentation, the findings are mainly consistent with the literature, but some unexpected findings also exist. Overall, the performance management in companies researched is effective, but still has some problems need improving and suggestions are provided to further development.